POPULATION DYNAMICS OF THE MAIN PELAGIC SPECIES EXPLOITED IN THE JAVA SEA: STOCK EVALUATION - Bambang Sadhotomo (Indonesian Fisheries Research Journal, 2006)
This study was based on length composition data collected from purse seine fleets operating in the Java Sea, and aimed to elaborate the state ofthe stock of the main species.